The Influence of Communication and Teamwork on the Work Productivity of NCVS 2.02 Sewing Department Employees at PT Adis Dimension Footwear, Tangerang Regency - Lestina, Lestina; Setiawan, Temmy; Putri, Narti Eka (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The purpose of this study was to determine the extent of the influence of communication and teamwork on the work productivity of employees in the Sewing NCVS 2.02 division at PT Adis Dimension Footwear, Tangerang Regency. This study uses a quantitative descriptive method. The population in this study were all employees in the Sewing NCVS 2.02 division at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 57 respondents. The technique used to determine the sample in this study was the simple random sampling technique. Meanwhile, to determine the number of representative samples in quantitative research, the formula used is the Slovin formula. The data collection techniques used were observation, questionnaires and documentation. The data analysis technique used multiple linear regression analysis using SPSS 26. The validity of the data was obtained through the t test (partial) and simultaneous F test. The results of this study indicate that (1) partially, communication significantly influences t on the work productivity of employees in the Sewing NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by the calculated t value> t table (5.412> 2.005) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected.(2) Partially, teamwork significantly influences the work productivity of employees in the Sewing NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by the calculated t value> t table (3.035> 2.005) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, communication and teamwork significantly influence the work productivity of employees in the Sewing NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (55.878>3.17) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected. Based on the results of the study, it can be concluded that the variables of communication and teamwork, both partially and simultaneously, have a significant influence on the work productivity of employees in the Sewing NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency.